Gambaran status vaksinasi human papillomavirus (HPV) dan faktor penghambat pada mahasiswi Fakultas Kedokteran Universitas Sam Ratulangi - Gultom, Cristin; Monintja, Tyrsa Christine Natalia; Ottay, Ronald Imanuel (Jurnal Kedokteran Komunitas dan Tropik, 2025)
Background: Human Papillomavirus (HPV) is the leading cause of cervical cancer, which is a global health problem for women, especially in Indonesia. Cervical cancer ranks fourth globally and second in Indonesia as the most common cancer in women in 2022. HPV vaccination is an effective primary prevention and is part of the WHO's global cervical cancer elimination strategy. HPV immunisation in Indonesia was integrated into BIAS in 2023. Medical students are among the high-risk age groups for HPV infection and play a role as future healthcare professionals in raising public awareness about cervical cancer, HPV, and cervical cancer prevention. Aim: To determine the status of human papillomavirus (HPV) vaccination and the inhibiting factors among female students at the Faculty of Medicine, Sam Ratulangi University. Methods: Descriptive research with a quantitative approach and a cross-sectional design through the distribution of a Google Forms questionnaire to 276 female students from the 2025 cohort of the Faculty of Medicine at Unsrat. The analysis used is univariate analysis. Results: A total of 114 respondents (87.8%) had not yet received the HPV vaccine, while 20 respondents (12.2%) had. The dominant barriers were not knowing where to get the HPV vaccine (67.4%), not having time for the HPV vaccine (65.3%), and not receiving a recommendation from healthcare professionals (64.6%). Conclusion: The majority of female students in the 2025 class of the Faculty of Medicine at Unsrat had not yet been vaccinated, with the dominant barrier being not knowing where to get the HPV vaccine.